Knockout of thyroid hormone receptor alpha a (thraa) enhances cardiac regeneration in zebrafish through metabolic and hypoxic regulation - Man Yee Cheung; Chunmei Jiang; Imtiaz Ul Hassan; Hui Wang; Donghao Guo; Daniel Wuyang Dio; Huan Yan; Jianmin Sun; Xufeng Qi; Dongqing Cai; Wei Ge; Sheue-yann Cheng; et al. (Cell Communication and Signaling)
Abstract Background Thyroid hormone (TH) signaling drives cardiomyocyte (CM) maturation in endothermic animals. Elevated TH levels, coupled with increased basal metabolism, promote CM cell cycle exit and polyploidization, thus limiting heart regenerative potential. However, a comprehensive understanding of TH and its receptors, thyroid hormone receptors (TRs), orchestrating with other regulatory processes for heart regeneration, such as the hypoxia signaling pathway and post-injury metabolic switches, remains elusive. Results Here, we investigated the molecular mechanisms of TH signaling in heart regeneration using a time-course sequencing experiment. We assessed heart regeneration capacity in thyroid hormone receptor alpha a (thraa) mutant zebrafish, which carry an 8-bp insertion that leads to truncation of the Thraa protein and impaired TH signaling. The thraa + 8 bp mutant zebrafish exhibited an enhanced heart regenerative response. Our study showed that, in thraa +/– mutants, a transiently augmented inflammatory response and an extended CM proliferative window are associated with metabolic switches across different phases. Moreover, we found that thraa transcriptionally regulates hypoxia-inducible factor 3 subunit alpha (hif3a), and its knockout in zebrafish impairs heart regeneration. Conclusions In conclusion, our study highlights the role of TH signaling via thraa in modulating zebrafish heart regeneration through metabolic regulation, inflammation, cardiac tissue regeneration, and its interplay with hif3a.